To pivot or not to pivot? - Barron, A. (1999)
The pivot is a maneuver that entails gliding around the corner, or part of the corner, on one skate; on the right foot and inside edge. It is a skill that should be learned by a young skater only after the proper technique of skating the entire track has been perfected. The pivot is sometimes abused in that if it is used at an incorrect time it causes a skater to lose speed, or not give a tactical advantage. The pivot occurs when two things change in the normal corner technique: 1) the skater glides around the corner/or part of the corner on the right foot inside edge, 2) and the skater "puts his/her hip into the corner A number of reasons is given to do the privot.